Assessment of inhibitory action of tea extract on human salivary amylase - Mehak Mahajan; Vijay Kumar Shah
Tea, an aromatic beverage from Camellia sinensis, is the second most consumed drink after water. The different types of tea include black, green, oolong, etc. Salivary amylase is an enzyme that helps digestion by breaking down polysaccharides into smaller molecules, contributing to elevated blood glucose levels and postprandial hyperglycemia. The scientific community is exploring natural inhibitors of amylase to slow down starch digestion and lower postprandial blood glucose levels for diabetes management. Plant-derived ga(B-amylase inhibitors are gaining popularity as safe and cost-effective alternatives. The current study included the effect of tea extract on the action of human salivary amylase. The result demonstrated that the extract slowed down human salivary amylase activity in a dose-dependent manner. At the concentration of 1% tea extract, the achromatic point was reached in an hour, while in the control sample, it was achieved within 5 minutes. In conclusion, tea consumption affects the attributes of human saliva by inhibiting the activity of salivary amylase, thereby affecting the digestion of starch. Thus, tea could potentially be used to manage glucose levels in diabetes patients.s